The Specificity Principle in Young Dual Language Learners' English Development. Issue 5 (19th March 2021) - Sun, He; Bornstein, Marc H.; Esposito, Gianluca
Abstract : This study employs the Specificity Principle to examine the relative impacts of external (input quantity at home and at school, number of books and reading frequency at home, teachers' degree and experience, language usage, socioeconomic status) and internal factors (children's working memory, nonverbal intelligence, learning‐related social‐skills, chronological age, gender) on children's English‐language development in phonological awareness (PA), receptive vocabulary (RV), and word reading (WR). Altogether, 736 four‐ to five‐year‐old Singaporean Mandarin‐English speaking kindergarteners were assessed twice longitudinally. Their English‐language PA, RV, and WR development was predicted using the eight external factors and five internal factors with Bayesian least absolute shrinkage and selection operators. Internal factors explained more variance than external factors in all three language domains. External factors had their largest impact on RV.